Pengaruh Struktur Modal, Profitabilitas, Ukuran Perusahaan, dan Likuiditas Terhadap Nilai Perusahaan (Studi Pada Perusahaan perbankan yang Terdaftar di BEI Periode 2010-2014) - Efendi, Ifin Aria; , Dr. Erma Setiawati, Ak, MM (2016)
This study aimed is to examine the effect of capital structure, profitability, company size and liquidity of the company's value. Population in this study were banking companies listed on the Stock Exchange 2010-2014.The sample in this study were selected using purposive sampling method. The sample used in this study are 21 companies. This study uses secondary data obtained through ICMD quantitative and summary financial statements listed on the Stock Exchange. Technical analysis of the data used is multiple linear regression. The results of this study indicate that capital structure has no effect on corporate value, profitability and company size have positive effect on the value of the company, and liquidity have negative effect on the value of the company.